Ancient history education through project-based learning - María-Pilar Molina-Torres (The Journal of Classics Teaching)
The effectiveness of teaching strategies and resources that promote meaningful content learning is most pronounced when active methods such as project-based learning (PBL) are used to teach Ancient History (Molina, 2020, 53). Therefore, this study focuses on a comprehensive assessment of the methodological and historical competences acquired by students enrolled in the secondary education teacher training programme at the University of Cordoba (Spain). The research, which is non-experimental and quantitative, uses a Likert-type scale and involves the participation of 201 Masters students who have completed the course ‘Learning and Teaching Social Sciences’. The results of the statistical analysis show a positive evaluation of PBL in terms of historical understanding and its effectiveness in improving historical awareness. It is crucial to emphasise the advantages of active and collaborative learning inherent in PBL. However, it is also imperative to acknowledge the challenges that students face in applying their methodological knowledge to the secondary school setting. The transition from theoretical understanding to practical implementation is a significant hurdle for many students aspiring to a career in education. These findings underline the importance of promoting the seamless integration of innovative pedagogical approaches into teacher training programmes in order to effectively address the specific challenges of teaching antiquity in an educational context. Finally, this research was made possible by the Ministry of Science and Innovation's ‘Prueba de Concepto’ project, funded by the European Union under grant number PDC2022-133123-I00, and also by the CLIOGEN project (GINDO-UB/187) on Ancient History.